Light scattering and absorption in pigmented coating : theory and experiments - Vargas Castro, William E. 1960- (Uppsala : Acta Universtatis Upsaliensis, 1997)
Tesis (doctorado)--Uppsala University, 1997
Keywords: PELICULAS DELGADAS; POLIMEROS